Unsupervised Domain Adaptation for Brain Vessel Segmentation Through Transwarp Contrastive Learning - Lin, Fengming; Xia, Yan; Deo, Yash; Macraild, Michael; Dou, Haoran; Liu, Qiongyao; Wu, Kun; Ravikumar, Nishant; Frangi, Alejandro F. (Proceedings - International Symposium on Biomedical Imaging, 2024)
Unsupervised domain adaptation (UDA) aims to align the labelled source distribution with the unlabelled target distribution to obtain domain-invariant predictive models. Since cross-modality medical data exhibit significant intra and interdomain shifts and most are unlabelled, UDA is more important while challenging in medical image analysis. This paper proposes a simple yet potent contrastive learning frame-work for UDA to narrow the inter-domain gap between labelled source and unlabelled target distribution. Our method is validated on cerebral vessel datasets. Experimental results show that our approach can learn latent features from labelled 3DRA modality data and improve vessel segmentation performance in unlabelled MRA modality data.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Cerebral Vessel Segmentation; Contrastive Learning; Unsupervised Domain Adaptation